Aspects of humoral and cell-mediated immune responses in calves experimentally infected with Mycobacterium bovis strains - NAYAK, SUJIT; VERMA, RISHENDRA; JOSHI, BEENU; VENKATESAN, K (The Indian Journal of Animal Sciences, 2014)
Calves (5; CI to C5) were infected intravenously with 1 mg (wet weight) of freshly grown cultures of M.bovis strain AN5 and a field strain of Mbovis (3/87) in 5 ml normal saline solution (NSS). One calf(C6) was administered intravenously 5 ml ofNSS. Calves C3 and C6 served as control for the tuberculin test since calfC3 (infected) was not tuberculin tested. The calves C1, C2, C4, C5 and C6 were tuberculin tested with 0.1 ml (2000TU) of PPO of Mbovis AN5 origin at -14 day. 31 day, 76 day and 112 day. Sera from these calves and calf C3 were collected at -14 day, -7day and 0 day prior to infection and at Weekly intervals from 7 day onwards up to 119 day post inoculation. The sera were assayed for the level of(IgG) antibodies by ELISA using 3 antigens, viz. PPD, heat-killed sonicated and M bovis AN5 species-specific phenolic glycolipid (PGL). The study showed a rise in the IgG level at 7 day which persisted up to 14 day, again rose at 42 day to 76 day and then after 112 day post inoculation in calves CI, C2, C4 and C5 when assayed by ELlSA with above PPO and heat killed sonicated antigens. The early rise in IgG could not be detected by PGL antigen. however, the IgG could be deiected in these calves from 56 or 63 days which reached plateau after 77 or 91 days. The antibody level in calf C3 (not tuberculin tested) rose from 105 day post inoculation. whereas. no rise in IgG level could be seen in control calf C6 (uninfected). Titration of sera from calves by ELlSA with 3 antigens showed that a minimum of320-640 titre existed and no diagnostic titre could be attributed. On -14 day no appreciable increase in skin thickness was seen in all calves. On 31 day, PPO skin response in CI, C2, C4 and C5 was positive (> 5 mm). The skin responst: on subsequent tuberculin testing at 76 day and 122 day was not elevated. The results of cell-mediated and humoral immune responses, suggested a heterogenous humoral response in calves and an inverse relationship between cell-mediated and humoral response.